1999
DOI: 10.1046/j.1464-5491.1999.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of risk of developing diabetes mellitus among siblings of Type 2 diabetic patients

Abstract: A perception of reduced vulnerability to diabetes may occur due to unawareness of risk or minimization of risk. Feelings of invulnerability may affect emotional response to a subsequent result. It is not known whether providing more information about the risk of developing diabetes prior to screening would affect outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…CONCLUSIONS -In the present study, perceptions of risk for diabetes among offspring were higher compared with previous research involving both patients and offspring (7)(8)(9). Two possible causes may contribute to this higher risk perception.…”
Section: Research Design Andcontrasting
confidence: 65%
“…CONCLUSIONS -In the present study, perceptions of risk for diabetes among offspring were higher compared with previous research involving both patients and offspring (7)(8)(9). Two possible causes may contribute to this higher risk perception.…”
Section: Research Design Andcontrasting
confidence: 65%
“…Insulin concentrations at time 0,20,30, 40, 50, 60, 90, 120 and 180 min predicted (p < 0.05) the development of diabetes while insulin concentrations at time 1, 3, 5 and 10 min did not predict (p > 0.05) the development of diabetes in univariate logistic regression according to Wald test statistics (Table 1). Glucose concentrations at time 0, 1, 3,5,10,20,30, 40, 50, 60, 90, 120 and 180 min predicted the development of diabetes (p < 0.05) in univariate logistic regression analysis ( (Table 3). Glucose concentration at 90 min and gender were not significant (p > 0.05) predictors of development of type-2 diabetes according to the Wald statistics (Table 3) in the full model.…”
Section: Resultsmentioning
confidence: 99%
“…The diabetes prevalence in subjects with BMI < 25 kg/m 2 was 3.1% followed by 5.9% for subjects with BMI from 25 to 29.9 kg/m 2 and for subjects with BMI ≥ 30 kg/m 2 , the prevalence of diabetes was 11.2% [2]. Thus the magnitude of increased risk is greater for family history than for obesity per se.Although family history is a risk factor for diabetes, various studies have shown that fewer than 40% of people with a family history of the disease actually perceive themselves to be at an increased risk of developing diabetes compared to those with no family history of diabetes [7][8][9][10][11]. Therefore, altering risk perception is a potential target for intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Risk perception: studies show that risk perceptions are related to risk awareness (Farmer, Levy, & Turner, 1999). Risk perceptions matter in different ways according to the type of behaviours, namely whether they are ongoing or repeated (e.g., condom use) (Reid & Aiken, 2011), intermittent (e.g., vaccines) (Brewer et al, 2007;Nexøe, Kragstrup, & Søgaard, 1999) and new (e.g., a new colonoscopy and new habits) (Dillard, Ferrer, Ubel, & Fagerlin, 2012;Nexøe et al, 1999).…”
mentioning
confidence: 99%